2016
DOI: 10.1089/brain.2014.0328
|View full text |Cite
|
Sign up to set email alerts
|

Exercise Therapy for Parkinson's Disease: Pedaling Rate Is Related to Changes in Motor Connectivity

Abstract: Forced-rate lower-extremity exercise has recently emerged as a potential safe and low-cost therapy for Parkinson's disease (PD). The efficacy is believed to be dependent on pedaling rate, with rates above the subjects' voluntary exercise rates being most beneficial. In this study, we use functional connectivity magnetic resonance imaging (MRI) to further elucidate the mechanism underlying this effect. Twenty-seven PD patients were randomized to complete 8 weeks of forced-rate exercise (FE) or voluntary-rate ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
60
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(62 citation statements)
references
References 51 publications
(76 reference statements)
1
60
0
Order By: Relevance
“…It is important to note that the FE approach required active participation from the participant and that cycling was not passive. The motor assisted the individual in achieving a pedaling rate 30% greater than their preferred voluntary rate as determined during CPX testing, a percentage increase that resulted in global motor improvements in our previous work with PD [22, 27]. For both exercise groups, cadence in revolutions per minute (rpm) and heart rate were recorded for each session.…”
Section: Methodsmentioning
confidence: 99%
“…It is important to note that the FE approach required active participation from the participant and that cycling was not passive. The motor assisted the individual in achieving a pedaling rate 30% greater than their preferred voluntary rate as determined during CPX testing, a percentage increase that resulted in global motor improvements in our previous work with PD [22, 27]. For both exercise groups, cadence in revolutions per minute (rpm) and heart rate were recorded for each session.…”
Section: Methodsmentioning
confidence: 99%
“…In addition to changes in the magnitude of brain activity in M1, it has become clearer that PD patients also exhibit disruptions of the pattern of functional connectivity between cortical and subcortical motor regions . The abnormal cortico‐subcortical connectivity can be boosted, with recent results demonstrating that an improvement in pedaling rate in PD who had undergone exercise therapy was related to an increase in functional connectivity between M1 and thalamus . A linear increase in motor‐related connectivity between the putamen and M1 was also detected following levodopa intake in a cohort of PD who later developed levodopa‐induced dyskinesia .…”
Section: Functional Changes In the Motor Cortex Of Pdmentioning
confidence: 99%
“…This research identified the need for further studies with the CF intervention in parkinsonians, mainly related to the intensity appropriate for favorable cardiovascular effects. It is possible to identify research models with aerobic training in parkinsonians, but aimed at different objectives [29,30,32]. Thus, the analysis of the effectiveness of the training circuit as a method of conditioning becomes relevant due to the lack of the subject in the literature; however, this analysis in a restricted number of participants is a limitation of this study [31].…”
Section: Discussionmentioning
confidence: 99%